320 Genetic Compensation as a mechanism underlying patients with Rare ALS. (April 2022) - Gomez, Adriana Morales; Staff, Nathan; Ekker, Stephen C.
Abstract : OBJECTIVES/GOALS: Rare mutations in CHCHD10 gene are found in 1% of patients with familial Amyotrophic lateral sclerosis (ALS). The overall goal of this study is to utilize induced pluripotent stem cells (iPSCs) as an in vitro model organism for rare ALS variants to evaluate the mechanism of transcription adaptation of CHCHD10/2 as a potential therapeutic. METHODS/STUDY POPULATION: Point mutations on normal iPSCs was performed via Donorguide CRISPR/Cas9. The single stranded RNA/DNA donors contain genetic alterations of CHCHD10: Pro12Ser, Arg15Leu, Pro23Leu, Pro34Ser, Ser59Leu, Gly66Val, Pro80Leu, Tyr92Cys and Gln102His. Ribonucleoprotein electroporation was used to transfect iPSCs and DNA sequencing was used to validate gene editing. To validate transcriptional adaption, changes in levels of protein and gene expression were measured via immunoblot and quantification of CHCHD10 and CHCHCD2 was performed from whole cells lysates of the edited iPSCs. RESULTS/ANTICIPATED RESULTS: We anticipate that CHCHD2 transcriptional adaptation can functionally compensate for the locus loss of function of CHCHD10. This mechanism of transcriptional adaptation may contribute to an explanation for variation in clinical manifestations of patient phenotypes. DISCUSSION/SIGNIFICANCE: This study supplies further evidence for genetic modification as a treatment option for diseases with point mutation causal or enabling mechanisms, including some variants of ALS. Future work will explore the gene-correction from an ALS patient with a known CHCHD10-R15L variant.